In situ growth of CuO nanoparticles onto cotton textiles - Roman, Luz E. (2020)
The application of nanotechnology has gained importance in the finishing of textile products, imparting them functional properties, which are achieved without affecting the textile. A novel method was developed for the in situ growth of CuO nanoparticles (NPs) onto cotton textiles by the exhaust dyeing method. For functionalised textiles, a constant sodium hydroxide concentration (0.4 g l(-1)) and different percentages of on-weight-fabric (% owf) of copper acetate were used. The textiles were microbiologically evaluated, the laundering durability was assessed and their UV protection factor (UPF) was determined. In addition, their CIE L*a*b* colour coordinates and colour strength (K/S) were studied. The results determined that NPs on the textile were CuO and were distributed randomly on the cotton fibre surface. The functionalised textiles with CuO NPs had percentages of bacterial reduction against Escherichia coli (ATCC 25922) between 89.7 and 99.7% and showed an improvement in the UPF of cotton from approximately 7 to 32. The CuO NP content on the textile was inversely correlated with the L* value and directly correlated with the a* and b* values and the K/S parameter.